Analytical Issues in Debt. (Washington, D.C. : International Monetary Fund, 1989)
This book, edited by Jacob A. Frenkel, Michael P. Dooley, and Peter Wickham, presents a sample of the work of the IMF and that of world-renowned scholars on the analytical issues surrounding the explosion of countries with debt-servicing difficulties and describes debt initiatives and debt-reduction techniques that hold the best promise for finding a lasting solution to the problems of debtor countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet